The Effect of Work Stress, Communication, Work Ability on Employee Performance Through Job Satisfaction at PT. Global Way Indonesia in Pasuruan - Sahid Sumitro (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Research aims to determine the Effect of Work Stress, Communication, Work Ability on Employee Performance through Job Satisfaction at PT. Global Way Indonesia Pasuruan. The population and samples in this study were employees at PT. Global Way Indonesia Pasuruan as many as 100 respondents.